Information Technology Management in Improving Teacher Performance Productivity in the Digital Era of IT Middle Schools in the Riau Islands Province - Rizki Firmanda; Risnita; Iskandar Nazari (Maneggio, 2026)
This study aims to analyze information technology management in improving teacher performance productivity in the digital era at Integrated Islamic Junior High Schools in Riau Islands Province, focusing on planning, infrastructure, implementation, security, information technology evaluation, and teacher performance productivity including teaching quality, time efficiency, learning innovation, commitment, and collaboration. The research employed a qualitative approach with a case study method conducted at SMP IT Ulil Albab Batam, SMP IT As Sakinah Tanjungpinang, and SMP IT Bahtera Insani Bintan. Research subjects included teachers, principals, vice principals, IT coordinators, students, and parents selected through purposive sampling until data saturation was achieved. Data were collected through participant observation, semi-structured interviews, documentation studies, and focus group discussions, then analyzed using an interactive analysis model with two-stage coding. Data validity was ensured through triangulation, member checking, and thick description. Results show that 70% of schools have strategic IT plans, although implementation varies with significant infrastructure gaps between schools. Teacher performance productivity increased with 80-85% of students finding materials easier to understand, 78% of teachers more efficient in time management, and 90% of teachers committed to improving teaching quality through technology. Supporting factors include management support, continuous training, and adequate infrastructure, while inhibiting factors include budget constraints, lack of digital competence, and low cybersecurity awareness. This study proves that effective information technology management is key to improving teacher performance productivity, requiring a holistic approach including strategic planning, competency development, and continuous evaluation to create a sustainable digital learning ecosystem.